Dampak Dinamika Pertumbuhan Penduduk Terhadap Kebersihan Lingkungan Pesisir Desa Poka Rumah Tiga Kecamatan Teluk Ambon - Karmila Rahakbau; Edward Gland Tetelepta; Susan Evelin Manakane (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2025)
This study aims to analyze the impact of population growth on coastal environmental cleanliness in Poka Rumah Tiga Village, Teluk Ambon District. Rapid population growth often results in increased waste production and pressure on coastal ecosystems. The research method used is a descriptive quantitative approach with surveys conducted through questionnaires distributed to 200 respondents. The study findings indicate that rapid population growth has led to a significant increase in unmanaged household waste. The primary contributing factors include a lack of community awareness regarding waste management and insufficient waste management infrastructure. Further analysis shows that communities with higher education levels tend to have better environmental awareness. In conclusion, a collaborative effort among the government, community, and private sector is needed to develop more effective waste management strategies to maintain coastal environmental cleanliness.